ナンキョク キキュウ ニヨル デンバ ト オーロラ Xセン ノ カンソク b. デンバ ト デンリュウ ケイ ダイ 1カイ キョクイキ ニオケル デンリケン ジキケン ソウゴウ カンソク シンポジウム PART 1 - 小川, 俊雄; オガワ, トシオ; 小玉, 正弘; コダマ, マサヒロ; 福西, 浩; フクニシ, ヒロシ; 松尾, 敏郎; マツオ, トシロウ; 芳野, 赳夫; ヨシノ, タケオ; OGAWA, Toshio; KODAMA, Masahiro; et al. (国立極地研究所, 1979)
P(論文) 1976年12月12日11時38分UT,南極昭和基地から5000m^3のプラスチック気球を飛揚し,約10時間にわたって成層圏における水平電場とオーロラX線(>25 keV)の同時観測を行った.観測時間中,午後のオーロラ帯の東向きシェット電流に対応する地磁気サブストームがあり,電場は10mV/mから40mV/mに増加した.電場の南向き成分と地磁気水平分力が,また,電場の西向き成分と偏角が対応する変化を示した.観測されたオーロラX線は全天にわたってほとんど一様なdiffuse型のものであった.サブストーム中3回オーロラX線が増大し,そのうちの1回には明らかに南向き電場の減少が対応したが,後の2回については,はっきりした電場の変化はなかった.サブストームに伴って電場の方向には特別の変化はなかった.観測された電場の1時間平均値は明らかなS_q^p型を示した.昭和基地の磁場変化と観測された電場変化から電離層電気伝導度を計算し,1-10mhoの値を得た.サブストーム時にはHall伝導度が増加した. A plastic balloon of 5000 m^3 was launched at Syowa Station (L=61), Antarctica, at 1138 UT on December 12, 1976, and the horizontal electric field and auroral X-rays (>25 keV) were simultaneously measured for about 10 hours m the stratosphere. During the balloon flight a weak geomagnetic substorm occurred corresponding to the eastward electrojet in the afternoon side of the auroral zone, and the electric field increased from 10 mV/m to 40 mV/m. There were good correspondences between the southward electric field and geomagnetic horizontal component and between the westward electric field and declination. Observed auroral X-rays were homogeneous throughout the all sky and of diffuse type. The X-rays were enhanced three times during the substorm. The electric field clearly decreased on the second X-rays event but there was no clear change on the other two events. There was no special change in the electric field direction during the geomagnetic substorm. One hour averages of the observed electric field show a clear S_q^p pattern. The height-integrated conductivities were calculated from the observed electric field and the geomagnetic variations at Syowa Station, getting the values of 1-10 mho. The Hall conductivity increased during the substorm. departmental bulletin paper